Free Trade Agreement (FTA) and Employment - Sumit Chowdhury; Sugata Marjit; Gouranga Das (CESifo GmbH, 2025)
While FTA negotiations are proliferating, our paper shows that targeting the appropriate sector is crucial for generating employment opportunities subsequent to FTA. In particular, we show that, countering conventional wisdom, targeting skill-biased exports and not the sector that employs unskilled workers who usually constitute the large core of the unemployed, could ameliorate the unemployment problem. The mechanism hinges on how the demand for goods produced by the non-traded sector is stimulated by such a policy. If targeting the skilled sector with an FTA can stimulate local demand more, employment impact of FTA may be more significant.
Keywords: C52; D50; F16; J21; J31; 330; FTA; minimum wage; demand effect; non-tradable; employment; elasticity of substitution; factor-intensity